Chronic Candida dubliniensis meningitis in a lung transplant recipient - Sabina Herrera; Paolo Pavone; Deepali Kumar; Lianne Singer; Atul Humar; Cecilia Chaparro; Shaf Keshavjee; Shahid Husain; Coleman Rotstein (Medical Mycology Case Reports, 2019)
Candida spp. are common colonizers of the oral mucosa and respiratory tract in lung transplant recipients. Although thought to be non-pathogenic in most cases, donor derived infections related to Candida spp. have been described. Among the manifestations of invasive candidiasis, chronic meningitis is one of the rarest and one of the most challenging to diagnose, due to the indolence of the disease and the low yield of the CSF cultures. It is associated with severe morbidity and a high mortality. Fungal PCR and BD glucan assays can be assistance in its diagnosis, although these tests are not widely available. We report a case of a possible donor derived Candida dubliniensis infection in a lung transplant recipient, who initially presented with empyema that was treated successfully, but subsequently developed chronic meningitis. Diagnosis was delayed due to the low yield of CSF cultures, and was confirmed with fungal PCR and BD glucan assay. Keywords: Candida meningitis, Chronic meningitis, Candida dubliniensis, Lung transplant, Immunocompromised